Method to estimate rotational stiffness: Trial masses, virtual masses, and virtual springs. (7th July 2020) - Kim, Jun Gu; Nam, Kyoung-Uk; Kang, Yeon June
Abstract: This paper proposes a method to estimate the rotational stiffness at the coupled points of an assembled system. Conventional test-based rotational stiffness evaluation methods are sensitive to measurement errors and require a separate jig for testing. In contrast, as the proposed method uses the natural frequency shift phenomenon resulting from the addition of mass, the measurement error is relatively small, and accuracy is improved by excluding the interference of other modes. The proposed method also solves the complexity of the conventional method by changing the fixed condition of the system using frequency response function-based substructuring modeling; consequently, it does not require a dedicated jig for fixing. In this process, the concepts of trial mass, virtual mass, and virtual spring are introduced to systematically explain the proposed method and applied to the method using frequency shift. The results of experiments conducted on a vehicle shock absorber verify the utility of the proposed method. Highlights: Rotational stiffness is estimated by a natural frequency shift method. Interference from other modes are excluded when estimating rotational stiffness. FRF-based substructuring enables efficient and convenient experimentation. Concepts of virtual mass and virtual stiffness are proposed for testing convenient. Jigs are not required for rotational stiffness estimation.